1964
DOI: 10.1016/0029-5582(64)90425-0
|View full text |Cite
|
Sign up to set email alerts
|

A study of the gamma radiation produced in the alpha-particle bombardment of O16

Abstract: This thesis describes an investigation of gamma rays from the d 6 20 reaction (a., y)Ne • The excitation function for gamma radiation has been studied for laboratory alpha-particle energies Ea. from 4. 8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

1967
1967
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The authors of Ref. [22] observed a weak γ decay of this state in the presence of a large background. A broader level than in Ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors of Ref. [22] observed a weak γ decay of this state in the presence of a large background. A broader level than in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…For this state the adopted data in Ref. [6] are based on the results of a single older work [22]. The authors of Ref.…”
Section: Resultsmentioning
confidence: 99%
“…However, in view of technical problems in the j3-ray measurements we have preferred to make our analysis in terms of the superallowed transition of Na 20 to its analog in Ne 20 at 10.270±0.009 MeV. 7 For the Fermi part of this transition we have taken 8 ft-3060 ± 20 sec; for the Gamow-Teller part we have based ourselves on local systematics and taken the range ft = 6.3 xl0 4 -°° sec; this leads toft = 2990 ± 70 sec for the two together. For the Na 20 mass excess we have taken 6 The half-life of F 20 has been determined as 11.03 ±0.06 sec and J3 branches have been measured in the decay of Na 25 .…”
mentioning
confidence: 99%
“…[6] in the widths is marginally exceeds the error bars, the influence on the better fit is evident. The adopted data [6] for this level are based on the results of a single older work [22]. The authors [22] observed a weak γ decay of this state in the presence of a large background.…”
Section: Resultsmentioning
confidence: 99%
“…The adopted data [6] for this level are based on the results of a single older work [22]. The authors [22] observed a weak γ decay of this state in the presence of a large background. A broader level than in Ref.…”
Section: Resultsmentioning
confidence: 99%